The Past, Current Studies and Future of Organometallic 99mTc(CO)3 Labeled Peptides and Proteins - Piramoon, Majid; Jalal Hosseinimehr, Seyed (Current Pharmaceutical Design, 2016)
The labeling of biomolecule using 99mTc-tricarbonyl is an interesting tool for the diagnosis of diseases. This labeling startegy has several advantages as compared to other common radiolabeling techniques. This review is a complete overview of synthesis and chemistry of 99mTc-tricarbonyl molecule for labeling peptides and proteins. Also, the effect of ligand type on the stability and in vivo biodistribution of 99mTc-tricarbonyl labeled biomolecules are discussed. Chemistries of cyclopentadienyl and hexa histidine tag as two important bifunctional chelating agents (BFCA) are presented. The in vitro and in vivo behaviors of some 99mTc-tricarbonyl labeled peptides and proteins are explained. Preclinical outcomes revealed that these labeled compounds are biologically, kinetically and thermodynamically stable. Findings showed that 99mTc-tricarbonyl labeled biomolecules are promising tools for future clinical applications in image diagnosis.
Keywords: peptide